1994
DOI: 10.1007/bf01856879
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and music therapies for asthma among patients prestabilized on asthma medication

Abstract: One hundred six asthmatic subjects were medically prestabilized, then assigned to eight sessions of progressive relaxation, music, or a waiting-list. Seventy-two subjects completed treatment, of which 37 were evaluated in the laboratory with measures of forced expiratory flow. Relaxation-group subjects reported feeling the most deeply relaxed and produced the greatest improvement in forced expiratory flow during the last presession assessment period. All groups evidenced decreases in asthma symptoms. All group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 49 publications
(38 reference statements)
1
48
0
2
Order By: Relevance
“…Lehrer et al (1994) found that relaxation may not produce clinically significant effects on asthma when subjects are completely prestabilized on medication, which they referred to as a "floor effect." As this relates to the present investigation, two of the participants were prescribed daily long-term control medication.…”
Section: Discussionmentioning
confidence: 96%
“…Lehrer et al (1994) found that relaxation may not produce clinically significant effects on asthma when subjects are completely prestabilized on medication, which they referred to as a "floor effect." As this relates to the present investigation, two of the participants were prescribed daily long-term control medication.…”
Section: Discussionmentioning
confidence: 96%
“…However, it provides only indirect information on the resistive properties of the airway passages. Ambulatory monitoring is one of the major fields of application, using peak-flow meters or miniature electronic spirometers~e.g., Hyland, 1990; In the laboratory and in the clinic, spirometry has been used to assess effects of emotional states and relaxation therapy on asthma~e.g., Florin, Freudenberg, & Hollaender, 1985;Lehrer et al, 1994!. The primary disadvantage of spirometry is that the forced expiratory maneuvers take several minutes. Because the participant's effort and concentration may affect this measure, a minimum of three consecutive maneuvers are prescribed by current standards~ATS, 1995!.…”
Section: Potential and Limitations For Psychophysiologymentioning
confidence: 99%
“…However, related efficacy studies have shown contradictory results. Occasionally, the effect of muscular relaxation on pulmonary function variables proved to be significant on a statistical level, but its effect has rarely been of clinically significant magnitude [6, 7]. One example of sufficient peripheral relaxation was provided by Glaus and Kotses [8, 9], who found a reliable correlation between facial muscle tension and airway caliber.…”
Section: Introductionmentioning
confidence: 99%